2022
DOI: 10.1007/s11224-022-02035-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytovid19: a compilation of phytochemicals research in coronavirus

Abstract: The COVID-19 pandemic has immensely impacted global health causing colossal damage. The recent outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has increased the quest to explore phytochemicals as treatment options. We summarize phytochemicals with activity against various coronaviruses including SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV). We compiled 705 phytochemical compounds through text mining of 893 PubMed articles. The physicochemical properties includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It has been reported that a vast number of in silico molecular docking studies were performed using various flavonoids, [33] flavolignans, [34] stilbenolignan, [35] diterpenes [36] phenolic compounds [37] derived from phytochemicals [38,39] against SARS-CoV-2 proteins. The binding affinities of six ligands and reference molecules obtained from DockThor are given in Table 1.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…It has been reported that a vast number of in silico molecular docking studies were performed using various flavonoids, [33] flavolignans, [34] stilbenolignan, [35] diterpenes [36] phenolic compounds [37] derived from phytochemicals [38,39] against SARS-CoV-2 proteins. The binding affinities of six ligands and reference molecules obtained from DockThor are given in Table 1.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Highly correlated features were screened using the cor function, and linear models were fitted using the lm function in R software. 57 The potential of 4-chloro-3-formylcoumarin derivatives targeting human thymidine phosphorylase was analyzed by R-based QSAR. 58 Some more QSAR-based studies with phytochemicals are listed in Table 3.…”
Section: Example Of Qsar With Specific Phytochemicalsmentioning
confidence: 99%
“…R‐based QSAR analysis was performed on selected phytochemicals to explore their therapeutic potential for COVID‐19 treatment. Highly correlated features were screened using the cor function, and linear models were fitted using the lm function in R software 57 …”
Section: Example Of Qsar With Specific Phytochemicalsmentioning
confidence: 99%